Topography Correction for Distributed SAR Imaging: A Case Study for TerraSAR-X and TanDEM-X - Kraus, Thomas; Bachmann, Markus; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2018)
Multichannel synthetic aperture radar (SAR) image formation is a promising technique to mitigate the pulse repetition frequency (PRF) constraints inherent to single-channel SAR systems. The multichannel approach enables the acquisition of wide swathes while maintaining a high azimuth resolution. An important step during the multichannel processing for distributed SAR systems is the correction of the topographic phase. This phase is introduced by non-zero cross-track baselines between the antenna phase centers in a constellation or swarm of satellites. The paper in hand describes the processing approach which was exemplarily used for a multistatic experiment conducted with TerraSAR-X and TanDEM-X. Challenges with the correction of the topographic phase are highlighted and the impact of the cross-track baseline is discussed.
Keywords: Multistatic SAR; Multichannel SAR; TerraSAR-X; TanDEM-X; Topography